2011
DOI: 10.1186/gb-2011-12-12-r123
|View full text |Cite
|
Sign up to set email alerts
|

Caenorhabditis elegans Heterochromatin protein 1 (HPL-2) links developmental plasticity, longevity and lipid metabolism

Abstract: BackgroundHeterochromatin protein 1 (HP1) family proteins have a well-characterized role in heterochromatin packaging and gene regulation. Their function in organismal development, however, is less well understood. Here we used genome-wide expression profiling to assess novel functions of the Caenorhabditis elegans HP1 homolog HPL-2 at specific developmental stages.ResultsWe show that HPL-2 regulates the expression of germline genes, extracellular matrix components and genes involved in lipid metabolism. Compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 108 publications
(135 reference statements)
0
30
0
Order By: Relevance
“…Therefore, the absence of HPL-2 improves survival following the induction of acute ER stress by two distinct stressors. Importantly, increased resistance to ER stress does not reflect a general resistance to stress conditions, as hpl-2 mutants are inheritently sensitive to thermal stress (8), more sensitive to osmotic stress (10), but unaltered in their response to oxidative stress (7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the absence of HPL-2 improves survival following the induction of acute ER stress by two distinct stressors. Importantly, increased resistance to ER stress does not reflect a general resistance to stress conditions, as hpl-2 mutants are inheritently sensitive to thermal stress (8), more sensitive to osmotic stress (10), but unaltered in their response to oxidative stress (7).…”
Section: Resultsmentioning
confidence: 99%
“…Heterochromatin protein 1 (HP1) family proteins are conserved epigenetic regulators that control gene expression depending on the chromatin context (6). We have previously shown that the Caenorhabditis elegans HP1 homolog heterochromatin protein like-2 (HPL-2) plays a regulatory role in the dauer decision, an alternative developmental program that worms undergo under stressful conditions (7). In this study, we show that animals lacking HPL-2 are more resistant to induced ER stress, an effect mediated by the XBP-1/IRE-1 branch of the UPR and autophagy.…”
mentioning
confidence: 99%
“…However, we could not detect ectopic PGL-1 or HTP-3 in these worms. hpl-2 mutants were previously reported to have a modest increase in lifespan and to express genes that control dauer formation, lipid metabolism, and longevity in addition to germ-line genes in their soma (25). Raising synMuv B mutants at 24°C caused a dramatic increase in the level of ectopic germ-line gene expression, but did not result in an increase in lifespan (Fig.…”
Section: Synmuv B Mutants Ectopically Express Germ-line Factors But Amentioning
confidence: 99%
“…Despite a clear connection between heterochromatin maintenance and lifespan extension (Feser et al ., 2010; Meister et al ., 2011; Larson et al ., 2012; Jiang et al ., 2013), the cause of heterochromatin loss and how it leads to cellular damage and aging is not well understood. Generally speaking, heterochromatin loss would lead to a mis‐expression of genes that are normally repressed, which could result in age‐ associated cellular defects.…”
Section: Introductionmentioning
confidence: 99%